The Impact of Corona Virus (Covid-19) on E-Business in Pakistan. - KHAN, ARMAN; LIAQUAT, SAMMAN; SHEIKH, JAVED; PIRZADO, ALI AKBAR (The journal of contemporary issues in business and government, 2021)
This study documents the impact of Covid-19 on the E-Business in Pakistan.COVID-19 has a significant influence on public health and induces hasty changes in way of life, social distancing and home alienation, with social and economic implications. This indicates the socioeconomic expansion in the country has deteriorated. It's now messed up all sorts of industry on a global scale including the e-commerce sector. Big retailers had their stores turned off temporarily. In addition, due to declining footfalls, medium-sized and small- sized retailers are battling the situation. For fact, online companies are not off the list as well. Pakistan is also heavily impacted by them. Several e-commerce firms depend on China for most of their goods. In China, lockdown restrictions drastically decreased the production of goods, Thus it is expected to have a big impact on the Pakistan online sector, in particular Chinese goods. Primary research through a sample survey analysis is executed to boost outcomes.The result shows that because China is the biggest producer and the largest number of industries are locked. That’s why all the shipping processes which have hampered domestic economic growth are hindered by the influence of corona viruses.